Evidence for Crustal Magnetic Field Control of Ions Precipitating Into the Upper Atmosphere of Mars. Issue 10 (3rd October 2018) - Hara, Takuya; Luhmann, Janet G.; Leblanc, François; Curry, Shannon M.; Halekas, Jasper S.; Seki, Kanako; Brain, David A.; Harada, Yuki; Mcfadden, James P.; DiBraccio, Gina A.; Soobiah, Yasir I. J.; Mitchell, David L.; et al.
Abstract: We present the effects of the local magnetic field configurations on ions precipitating into the upper atmosphere of Mars using Mars Atmosphere and Volatile EvolutioN (MAVEN) observations. Precipitating pickup planetary heavy ions (O +, O 2 +, and CO 2 + ) are of particular interest in the Martian plasma environment because they potentially enhance the sputtering loss of ambient neutral particles. In addition, solar wind protons (and H + pickup ions) penetrate into the dayside atmosphere due to the direct interaction with the Martian obstacle. We present a statistical study showing that precipitating ion fluxes are typically enhanced by a factor of 2–3 under radial field configurations. We also show that the crustal fields have a shielding effect; the precipitating fluxes are significantly reduced by ∼50% under the strong crustal fields ( ≳ 100 nT), where the local magnetic field is oriented with a more horizontal component to the surface. These trends are seen consistently regardless of ion species, as well as the observed locations including dayside/nightside, subsolar longitudes, and ± E hemispheres in the Mars‐centered solar electric (MSE) coordinates. In particular, the local magnetic field configurations control precipitating ions with energies lower than a few keV, while precipitating high‐energy ion fluxes are likely independent of the local magnetic field configurations. Precipitating ion fluxes are known to vary by at least an order of magnitude depending on the upstream solar wind. Therefore, the local magnetic field configurations turn out to be the secondary factor in modulating precipitating ion fluxes at Mars. Key Points: We investigated the effects of the local crustal field configurations on precipitating ion fluxes into Mars Precipitating ion fluxes increase by a factor of 2–3 with the radial crustal fields while decrease by half with horizontal crustal fields The local crustal fields consistently control precipitating ion fluxes regardless of their species and the observed location